Spontaneous urinoma associated with ureteropelvic junction obstruction, solved by laparoscopic pyeloplasty: a case report - Gutiérrez, Perla G.; Chávez, David J. Á.; C. Rocha, Carla M.; Rivera, César A. G.; Blanquel, Juan L. S.; Cortés, Juan D. F. (International Surgery Journal, 2025)
Urinoma, a collection of extravasated urine in the perirenal or retroperitoneal space, often arises from obstructive uropathy, particularly in pediatric patients with congenital anomalies. This case report details a 15-year-old male presenting with acute abdominal pain due to ureteropelvic junction obstruction (UPJO), leading to a perirenal urinoma. The report outlines the clinical presentation, diagnostic challenges, and surgical management involving laparoscopic pyeloplasty. Despite postoperative complications, including hydronephrosis and the need for nephrostomy, the patient achieved successful outcomes with no recurrence of UPJO. This case emphasizes the complexities of diagnosing urinoma and the importance of tailored management strategies in similar cases.